2021
DOI: 10.1177/1096348020987634
|View full text |Cite
|
Sign up to set email alerts
|

Why Not Travel to Malaysia? Variations in Inbound Tourists’ Perceptions toward Halal-Friendly Destination Attributes

Abstract: The importance of halal tourism has prompted countries and business operators to place more emphasis on this lucrative sector. The purpose of this study is to investigate the effects of halal-friendly destination attributes on inbound tourists’ behavioral intention in the context of Malaysia. Furthermore, a comparative analysis was conducted to investigate the similarities and differences between Chinese and Indonesian Muslim tourists. A total of 666 observations were collected using surveys and the data sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 122 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…For example, disseminating information on the tourist attractions voluntarily and revisiting them (Lukuyu et al, 2012). Similarly, past tourism studies also found that post-visit evaluations would lead to higher levels of tourists' intentions to revisit a particular destination and recommend it to their families and friends (Azali et al, 2021). In this study, researchers explore the importance of influencing factors such as environmental issues and values in Ia customer's intention to return to a green resort.…”
Section: Revisit Intentionmentioning
confidence: 94%
“…For example, disseminating information on the tourist attractions voluntarily and revisiting them (Lukuyu et al, 2012). Similarly, past tourism studies also found that post-visit evaluations would lead to higher levels of tourists' intentions to revisit a particular destination and recommend it to their families and friends (Azali et al, 2021). In this study, researchers explore the importance of influencing factors such as environmental issues and values in Ia customer's intention to return to a green resort.…”
Section: Revisit Intentionmentioning
confidence: 94%
“…Several studies have been conducted using Malaysia as a case study. These studies have mainly examined the inbound tourism demand revolving around income, tourism prices, exchange rates, and Halal tourism (Azali et al, 2021; Tang, 2018; Wong, 2017; Zainuddin et al, 2016). However, they have not looked at destination competitiveness, the impact of institutional involvement, or the human agency’s role in destination competitiveness.…”
Section: Methodsmentioning
confidence: 99%
“…The friendliness of a destination is typically a factor considered by tourists when making decisions (Azali et al , 2021; Han et al , 2019). Anuar et al (2012) defined a friendly tourism destination as one that meets the needs and expectations of tourists without difficulty by integrating and optimizing the use of space, activities and products.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous destinations rely on friendly services to appeal to tourists; for example, countries such as Australia, Singapore, Malaysia and Hong Kong (Crotti and Misrahi, 2017) have introduced friendly services and successfully attracted tourists to their destinations. Destinations that provide tourist-friendly environments and services can increase the value perception (Al-Ansi and Han, 2019), satisfaction (Abd Jalil et al , 2013; Cruz-Milán, 2021) and behavioral intentions (Azali et al , 2021; Ho et al , 2022) of tourists. Therefore, developing a framework for friendly tourism destinations is critical for management and marketing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation